Religious Moderatism versus Conservatism in Indonesia: Controversy of ‘Islam Nusantara’ during Joko Widodo’s Administration - Hamdani (Tebuireng: Journal of Islamic Studies and Society, 2020)
The current trend of social and political fracture among Indonesian people has permeated many aspects of life, including religious domain. While moderate Muslims are still majority, the voice of conservative and also element of radical Muslim groups has shown a great militancy in campaigning for their agenda. Rivalry among those groups in the public discourse is unavoidable. This study examines the contested idea of ‘Islam Nusantara’ in the effort to campaign for moderate and friendly Islam in the early of Joko Widodo’s administration. Since conservative and radical factions have rejected the idea of Pancasila state, accusing of other Muslims of being kafir (apostasy) and the spirit to eliminate local cultures, their counterparts use different agenda and approach. The moderate Muslims use the concept of Islam Nusantara to campaign for the concept of Islam and nationalism, respect for diversity and cultural approaches. This study reveals the different point of view of Muslim groups regarding the concept and practice of Islam Nusantara which has become a controversy since the Nahdlatul Ulama (NU) used it as the main theme in the 33rd congress. Although ‘Islam Nusantara’ is not a new term in the discourse of Indonesian Islam, the contestation and consensus have produced a new fragmentation of religious opinions among Indonesian Muslims. This research aims to explore the sociology of knowledge among Indonesian Muslims whose inclination has been devided into two big streams of moderate and conservative wing.